L’avvio del Collegio Romano di Santa Maria / The beginnings of the Roman College of Santa Maria - María Isabel Montero Casado de Amezúa (Studia et Documenta)
The article describes the project of creating an international Center of Studies for women of Opus Dei which Josemaría Escrivá de Balaguer promoted and set in motion in 1953. After explaining briefly the present day situation of the Center, the article includes a study of the difficulties which the Founder encountered in carrying out the project. Information is given about the Campus, the early programs of study and the identity of the first students. Finally a brief overview is given of what might have been the day to day life of that First Class.